2018
DOI: 10.1186/s12889-018-6168-0
|View full text |Cite
|
Sign up to set email alerts
|

Does coffee drinking have beneficial effects on bone health of Taiwanese adults? A longitudinal study

Abstract: BackgroundResults from studies investigating the association between coffee consumption and osteoporosis or bone mineral density (BMD) have been inconsistent. This longitudinal study was performed to assess the effect of coffee drinking on bone health of Taiwanese adults.MethodsData were retrieved from the Li-Shin (Landseed) Hospital in Taoyuan City. In 2006, 6152 participants completed a questionnaire on coffee drinking and other lifestyle factors. In 2014, 5077 of them were followed up. Nonetheless, a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 42 publications
2
22
0
3
Order By: Relevance
“…Overweight and obesity were associated with a lower risk of osteoporosis in several studies. 1 , 11 , 13 , 45 - 48 Similar results were observed in our study. After stratification by the SOX6 rs297325 genotypes, these factors, however, remained significantly associated with osteoporosis only among those with the TC + CC genotype.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overweight and obesity were associated with a lower risk of osteoporosis in several studies. 1 , 11 , 13 , 45 - 48 Similar results were observed in our study. After stratification by the SOX6 rs297325 genotypes, these factors, however, remained significantly associated with osteoporosis only among those with the TC + CC genotype.…”
Section: Discussionsupporting
confidence: 92%
“…Age is an evident nonmodifiable primary risk factor for osteoporosis. 1 , 11 - 14 This was proven in this study as it remained significantly associated with an increased risk of osteoporosis regardless of the genotype. The capacity of the bone tissue to synthesize bone decreases as age increases.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…A recent study from the Taiwanese population examined the association between coffee consumption and T scores. The study revealed higher T scores in the coffee consumer group but half of the women in the study were premenopausal, so the evaluation of this study should be done carefully (32).…”
Section: Q2: How Coffee Consumption Affects Bmd (Bone Mineral Densitymentioning
confidence: 88%
“…On the other hand, high and moderate intake of coffee correlated with a higher T-score. Researchers observed a trend in a group with moderate consumption, which may suggest the T-score increases as the consumption of coffee increases [ 53 ]. Additionally, there was no association between coffee intake and occurrence of fractures or femoral neck fractures in women, although intake of four and more cups of coffee per day decreased BMD by 2–4% when compared to the subjects consuming less than one cup of coffee per day [ 54 ].…”
Section: Coffeementioning
confidence: 99%